Um estudo empírico sobre a contribuição do Performance Diagnostic Checklist para o processo de functional assessment em OBM - Euzebio, Valdemir Polidorio (2016)
The Behavior Analysis in organizations, which is also called Organizational Behavior Management - OBM or Performance Management - PM, is based on the same scientific principles upheld by the Radical Behaviorism. Among the more effective processes to find out variables maintaining problem behavior in organizations used nowadays, the functional assessment model has been considered the most complete by many researchers. This study aimed an investigation into the Performance Diagnostic Checklist PDC tool s contribution to the process of functional assessment through an empirical diagnosis made in a private company in the technology segment in São Paulo. For this study the translation of PDC tool for the Portuguese, some adjustments in the technical vocabulary and the digitization content to online format were held. Were participants in this study a high productivity team in sales comprised of six professionals (A Team), a team of average productivity in sales comprised of the same number of professionals (M Team) and a team of twenty-three professionals from different departments aimed at attainment of applicability tests of PDC tool (T Team). Were sent to the T Team participants electronic forms of PDC as well as a scale for assessing the applicability of this tool, then some adjustments were made at the PDC tool before it could be sent teams A and M that were the target of this study. The problem of this research comprised the finding of a relationship between performance measures declared by the researched company and the performance measures resulting from the PDC diagnosis for these two sales teams. An analysis of the 16 performance factors evaluated by the PDC and the selection of OBM interventions were also presented in this study. As a result, were identified interventions in six of these factors for the M team and three of these same factors had interventions identified to A Team. It can be said that the results obtained by the PDC ratified the performance measures declared by the researched company and also served as the basis for recommending interventions for both teams. It can also be said that the reliability of the PDC tool, after adjustments made during this study, was also achieved. New studies in Brazil that address the diagnosis and interventions through the PDC were also recommended considering the learned lessons in this research